Comparação entre medidas acústicas de vogais em provas de repetição e conversa espontânea - Berti, Larissa Cristina [UNESP]; Reato, Laiz Torres [UNESP] (My University, 2011)
The aim of this study is to compare acoustic measures (frequency, duration and intensity) of the vowels /i, a, u/ in repetition and spontaneous tasks. Recordings of words produced by ten children with typical language development in both controlled and spontaneous tasks were selected from a database. The vowels were selected and edited into individual files in the software PRAAT. Acoustic measures related to formant frequency (F1 and F2), intensity and duration of vowels in both contexts were extracted. The values obtained were compared by means of T Tests. In general, the acoustic analysis showed no differences between the two contexts of speech production. The few differences found can be explained by the presence of focus and/or hesitation phenomena during the speech productions. It is possible to use data from spontaneous context to analyze the vowels acoustically, provided that both the phonetic context of the vowel occurrence and the syllable stress of the vocalic segment are considered.
Comparison of acoustic measures of vowels in repetition and spontaneous tasks
Keywords: análise acústica; crianças; Fonética; vogais